Understanding the Lived Experiences of Athlete Elderly in COVID-19 Pandemic in Tehran (A Phenomenological Approach) - Rasoul Norouzi Seyed Hosseini (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Epidemics create extensive socio-behavioral changes in all areas, sport is no exception. The current study aimed at understanding the lived experience of athletic older adults from the Coronavirus Disease 2019 (COVID-19) pandemic.  Methods & Materials: The present qualitative research applied a phenomenological approach. The study participants were 16 athletic older adults in Tehran City, Iran who were selected by the purposive sampling method. Through in-depth and unstructured interviews, the required data were collected. The obtained data were analyzed using the seven-step Diekelman's (1993) approach.  Results: According to the obtained data, 4 categories of meanings were identified about the lived experiences of the explored elderly from the COVID-19 pandemic. These categories included the experiences of psychosocial isolation and thinking about death; the marginalization of older adultchr('39')s sports; mood swings and lifestyle changes, and finding opportunities for sports activism. Conclusion: These concepts of experiences in the life-world of athletic older adults in Tehran from the COVID-19 pandemic were the constitutions of their social action. In the case of proper analysis and application, they can be helpful in better managing professional sports in epidemics.